Tannin Extraction from Leaves of Some Plants - VONGDETH, Kingsadingthongkham; KEOXAMLOUANG, Xolo; BOUNMYXAI , Anoukone; SENGTHONGSA, Boudda (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This research, Tannin compound was extracted from cassava leaves, cueva leaves, jackfruit leaves, mango leaves and poninac leaves from Dongdok Village, Xaythany District, and Vientiane Capital. Using a single-soak extraction method and shaking with a stirrer using solvents as an extractor, such as distilled water, methanol (30%, 50%, 70%, and 95.85%), ethanol (30%, 50%, 70%, and 96.75%), acetone (30%, 50%, 70%, and 99.99%). The ratio between samples to solute was 5:50 g/mL extracted at room temperature with the extraction time of 13 hours (immersing 12 hours and shaking for 1 hour). The total amount of tannins in the sample was analyzed by reaction the folin-ciocalteu reagent and measuring the absorption of light at a wavelength of 762 nm. The results of the analysis of tannin content showed that the best extracts of tannins in all the samples were: tannin extract in poninac leave was 41.44 g/kg (50% acetone as an extract), the Jack fruit leaf was 39.56 g/kg (50% ethanol), the cueva leaf was 37.52 g/kg (30% acetone), the cassava leaf was 25.94 g/kg (70% acetone) and the extract of tannin from mango leaf was 22.24 g/kg (30% ethanol). Comparing the amount of tannin in the samples of cassava leaves, cueva leaves, jackfruit leaves, poninac leaves and mango leaves, it was found that poninac leaves had the highest amount of tannin. Following by samples of cueva leaves, jackfruit leaves, cassava leaves and mango leaves, respectively.